2013
DOI: 10.1073/pnas.1220108110
|View full text |Cite
|
Sign up to set email alerts
|

Engineering of a functional bone organ through endochondral ossification

Abstract: Embryonic development, lengthening, and repair of most bones proceed by endochondral ossification, namely through formation of a cartilage intermediate. It was previously demonstrated that adult human bone marrow-derived mesenchymal stem/stromal cells (hMSCs) can execute an endochondral program and ectopically generate mature bone. Here we hypothesized that hMSCs pushed through endochondral ossification can engineer a scaled-up ossicle with features of a "bone organ," including physiologically remodeled bone, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
300
2
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 282 publications
(315 citation statements)
references
References 32 publications
11
300
2
2
Order By: Relevance
“…An endochondral approach to bone tissue engineering may circumvent many of the issues associated with the intramembranous method, as cells progressing down the endochondral route are equipped to survive hypoxic conditions and release pro-angiogenic factors for the conversion of avascular tissue to vascularized tissue [8]. Indeed, it has been demonstrated that MSC-based cartilaginous grafts can be used to generate bone in vivo in both ectopic and orthotopic sites by executing such an endochondral program [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…An endochondral approach to bone tissue engineering may circumvent many of the issues associated with the intramembranous method, as cells progressing down the endochondral route are equipped to survive hypoxic conditions and release pro-angiogenic factors for the conversion of avascular tissue to vascularized tissue [8]. Indeed, it has been demonstrated that MSC-based cartilaginous grafts can be used to generate bone in vivo in both ectopic and orthotopic sites by executing such an endochondral program [8][9][10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, studies on hematopoiesis commonly rely on animal models to ensure the presence of an intact bone marrow microenvironment that enables normal physiologic marrow responses [12][13][14][15] . Furthermore, although it has been reported that bone marrow can be engineered in vivo [16][17][18][19] , no method exists to culture engineered bone marrow in vitro. To bridge the functional gap between in vivo and in vitro systems, we developed a method to produce a "bone marrow-on-a-chip" culture system that contains artificial bone and a living marrow, which is first generated in mice, and then explanted whole and maintained in vitro within a microfluidic device.…”
mentioning
confidence: 99%
“…Instead, the present protocols for chondrogenically differentiating MSCs result in the production of neocartilage that is characterized by hypertrophic differentiation (6)(7)(8)(9). Consequently, the newly formed cartilage undergoes endochondral ossification upon implantation (8,(10)(11)(12). In fact, it has been reported that, currently, the most efficient way to engineer new bone from multipotent progenitor cells is via implantation of in vitro-generated neocartilage (6).…”
mentioning
confidence: 99%